Na+/Ca2+ exchanger 2 is neuroprotective by exporting Ca2+ during a transient focal cerebral ischemia in the mouse - Jeon, Daejong; Chu, Kon; Jung, Keun-Hwa; Kim, Manho; Yoon, Byung-Woo; Lee, C. Justin; Oh, Uhtaek; Shin, Hee-Sup (ELSEVIER SCI LTD, 2008)
Na+/Ca2+ exchanger (NCX), by mediating Na+ and Ca2+, fluxes bi-directionally, assumes a role in controlling the Ca2+ homeostasis in the ischemic brain. It has been suggested that the three isoforms of NCX (NCX1, 2 and 3) may be differentially involved in permanent cerebral ischemia. However, the role of NCX2 has not been defined in ischemic reperfusion injury after a transient focal cerebral ischemia. Furthermore, it is not known whether NCX2 imports or exports intracellular Ca2+([Ca2+](i)) following ischemia and reperfusion. To define the role of NCX2 in ischemia and reperfusion, we examined mice lacking NCX2, in vivo and in vitro. After an in vitro ischemia, a significantly slower recovery in population spike amplitudes, a sustained elevation of [Ca2+](i) and an increased membrane depolarization were developed in the NCX2-deficient hippocampus. Moreover, a transient focal cerebral ischemia in vivo produced a larger infarction and more cell death in the NCX2-deficient mouse brain. In particular, in the wild type brain, NCX2-expressing neurons were largely spared from cell death after ischemia. Our results suggest that NCX2 exports Ca2+ in ischemia and thus protects neuronal cells from death by reducing [Ca2+](i) in the adult mouse brain. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: SODIUM-CALCIUM EXCHANGE; NA+-CA2+ EXCHANGER; BRAIN-REGIONS; RAT-BRAIN; IN-VITRO; EXPRESSION; NCX3; ISOFORMS; NEURONS; CLONING